Identification of annotated bioactive molecules that impair motility of the blood fluke Schistosoma mansoni. (August 2020) - Duguet, Thomas B.; Glebov, Anastasia; Hussain, Asimah; Kulkarni, Shashank; Mochalkin, Igor; Geary, Timothy G.; Rashid, Mohammed; Spangenberg, Thomas; Ribeiro, Paula
Abstract: Neglected tropical diseases are of growing worldwide concern and schistosomiasis, caused by parasitic flatworms, continues to be a major threat with more than 200 million people requiring preventive treatment. As praziquantel (PZQ) remains the treatment of choice, an urgent need for alternative treatments motivates research to identify new lead compounds that would complement PZQ by filling the therapeutic gaps associated with this treatment. Because impairing parasite neurotransmission remains a core strategy for control of parasitic helminths, we screened a library of 708 compounds with validated biological activity in humans on the blood fluke Schistosoma mansoni, measuring their effect on the motility on schistosomulae and adult worms. The primary phenotypic screen performed on schistosomulae identified 70 compounds that induced changes in viability and/or motility. Screening different concentrations and incubation times identified molecules with fast onset of activity on both life stages at low concentration (1 μM). To complement this study, similar assays were performed with chemical analogs of the cholinomimetic drug arecoline and the calcilytic molecule NPS-2143, two compounds that rapidly inhibited schistosome motility; 17 arecoline and 302 NPS-2143 analogs were tested to enlarge the pool of schistosomicidal molecules. Finally, validated hit compounds were tested on three functionally-validated neuroregulatory S. mansoni G-protein coupled receptors (GPCRs): Sm5HTR (serotonin-sensitive), SmGPR2 (histamine) and SmD2 (dopamine), revealing NPS-2143 and analogs as potent inhibitors of dopamine/epinine responses on both human and S. mansoni GPCRs. This study highlights the potential for repurposing known human therapeutic agents for potential schistosomicidal effects and expands the list of hits for further progression. Graphical abstract: Image 1 Highlights: Screening annotated bioactive molecules to ease new treatment search. Coupling motility recording of treated parasite and molecular target search. Exploiting chemical analogs to expand bioactive compound search. The larvicidal NPS-2143 acts on dopaminergic GPCRs.